Neighborhood socioeconomic status and food environment: a 20-year longitudinal latent class analysis among CARDIA participants - Richardson, Andrea S. (Health Place, 2014)
Cross-sectional studies suggest neighborhood socioeconomic (SES) disadvantage is associated with obesogenic food environments. Yet, it is unknown how exposure to neighborhood SES patterning through adulthood corresponds to food environments that also change over time. We used latent class analysis (LCA) to classify participants in the US-based Coronary Artery Risk Development in Young Adults study [n=5,114 at baseline 1985-1986 to 2005-2006] according to their longitudinal neighborhood SES residency patterns (upward, downward, stable high and stable low). For all classes of residents, the availability of fast food and non-fast food restaurants and supermarkets and convenience stores increased (p<0.001). Yet, socioeconomically disadvantaged neighborhood residents had fewer fast food and non-fast food restaurants, more convenience stores, and the same number of supermarkets in their neighborhoods than the advantaged residents. In addition to targeting the pervasive fast food restaurant and convenient store retail growth, improving neighborhood restaurant options for disadvantaged residents may reduce food environment disparities.